A CRITICAL EVALUATION OF A GOVERNMENT-SPONSORED HYBRID LEARNING PROGRAM FOR BRIDGING THE DIGITAL DIVIDE IN REMOTE EASTERN INDONESIA - Godlif Sianipar; Napat Chai; Pramila Kumari; Sanjay Sharma (Journal Neosantara Hybrid Learning, 2025)
The persistent digital divide across Indonesia’s eastern regions poses a major challenge to equitable access to education in the digital era. Despite national efforts to expand online learning infrastructure, disparities in connectivity, digital literacy, and resource availability continue to disadvantage students in remote areas. This study critically evaluates a government-sponsored hybrid learning program implemented in Eastern Indonesia that aimed to bridge this gap by combining online and offline learning modalities. The research investigates the program’s effectiveness in promoting equitable access, improving learning outcomes, and fostering digital inclusion among rural students and educators. A mixed-methods approach was employed, integrating quantitative surveys with 200 students and teachers across five districts and qualitative interviews with local education stakeholders. Quantitative data were analyzed using descriptive and inferential statistics, while qualitative data were examined through thematic analysis to capture contextual insights. The findings indicate that the hybrid learning model significantly improved digital literacy, student engagement, and instructional continuity in areas with limited internet access. However, challenges remained in infrastructure reliability, teacher readiness, and long-term sustainability due to uneven technological support and funding constraints. The study concludes that government-led hybrid learning initiatives can serve as effective transitional strategies for reducing educational inequality when supported by localized training and infrastructure development. It emphasizes the need for participatory policy design that integrates community-based solutions and capacity building to sustain the benefits of hybrid education in remote regions.